REFLEKSI ATAS REALITAS DAN PARADIGMA MASALAH SAMPAH | REFLECTION ABOUT REALITY AND PARADIGM PROBLEMS OF TRASH - Agustina Utami Ningsih (Jurnal Ledalero, 2017)
Abstract: Human activities always produce trash. The amount of trash continues to grow in line with population growth and technological developments. Trash has become an environmental crisis due to a lack of awareness and in Indonesia little serious effort has been made to process trash properly. The importance of a serious effort of trash management and self-development as a real human being is nothing other than a struggle to restore harmony between Creator, human beings, and the whole of creation. This paper reflects on the reality of trash as well as taking up the views and habits of people who are little concerned about handling trash although they already feel the adverse impact of trash on the environment. This study analyses data and the information obtained through observation of the trash problem, supported by data from written sources . Keywords: Trash, environment, human development, ecological repentance Abstrak: Kegiatan manusia selalu menghasilkan sampah. Peningkatan jumlah sampah terus bertambah seiring dengan pertambahan penduduk dan perkembangan teknologi. Sampah telah menjadi krisis lingkungan hidup karena kurangnya kesadaran dan belum seriusnya usaha pengolahan sampah dengan tepat. Pentingnya upaya serius pengolahan sampah yang tepat dan pengembangan diri sebagai manusia sejati adalah upaya mengembalikan harmoni antara Pencipta, manusia, dan semua ciptaan. Tulisan ini ingin merefleksikan realitas keberadaan sampah serta pandangan dan kebiasaan masyarakat yang kurang peduli terhadap penanganan sampah. Kajian ini dilakukan dengan metode interpretatif, yang menafsirkan dan memberi arti kepada data dan informasi yang didapatkan, berdasarkan dengan pengamatan masalah sampah dan keadaan faktual yang terjadi di dalam kebiasaan masyarakat terhadap sampah, didukung dengan fakta dari sumber literatur sebagai data dan informasi. Kata-kata kunci: sampah, lingkungan, pengembangan manusia, pertobatan ekologi